Inverse Models. Analog as Verification of the Digital (diségno, 2024)
The importance of representation as a space for model building has always been central to architectural practice. These models have served as a means of verifying ideas, according to a design approach that can be defined as “form-checking”. With the digital transition, this relationship is reversed and models are increasingly identified by parameters and information providing analysis, forecasts and identifying solutions, in an approach that thus becomes “form-finding”. If, however, the idea and form were initially “drawn” in the mind and on paper, today the idea and the figure remain in the mind, while the digital drawing finds the form according to the desired performance. The research presented here analyzes three case studies in which models stigmatize the relationships between ideation, verification and implementation. The first case study concerns the construction of the Ames room, an iconic theme of perception, created as a temporary pavilion, generated through generative algorithms, BIM models and digital fabrication. The second case study presents the creation of a test room, a model built to monitor in real-time and compare actual performance with data simulated by multi-objective algorithms. The third case study concerns experimental research on 3D printed wooden hygroscopic architectural elements, similar models that show the role of representation in the relationship between design, manufacturing and responsiveness.
Keywords: generative design; Ames room; digital fabrication; wooden pavilions; wood 3D printing